The quality of maternal nutrition and infant feeding counselling during antenatal care in South Asia - Harriet Torlesse; Rukundo K. Benedict; Hope C. Craig; Rebecca J. Stoltzfus (Wiley, 2021)
Abstract Antenatal care (ANC) provides a platform to counsel pregnant women on maternal nutrition and to prepare the mother to breastfeed. Recent reviews suggest that gaps in the coverage and quality of counselling during pregnancy may partly explain why services do not consistently translate to improved behavioural outcomes in South Asia. This scoping literature review collates evidence on the coverage and quality of counselling on maternal nutrition and infant feeding during ANC in five South Asian countries and the effectiveness of approaches to improve the quality of counselling. Coverage data were extracted from the most recent national surveys, and a scoping review of peer‐reviewed and grey literature (1990-2019) was conducted. Only Afghanistan and Pakistan have survey data on the coverage of counselling on both maternal nutrition and breastfeeding, nine studies described the quality of counselling and three studies assessed the effectiveness of interventions to improve the quality of services. This limited body of evidence suggests that inequalities in access to services, gaps in capacity building opportunities for frontline workers and the short duration and frequency of counselling contracts constrain quality, while the format, duration, frequency and content of health worker training, together with supportive supervision, are probable approaches to improve quality. Greater attention is needed to integrate indicators into monitoring and supervision mechanisms, periodic surveys and programme evaluations to assess the status of and track progress in improving quality and to build accountability for quality counselling, while research is needed to understand how best to assess and strengthen quality in specific settings.